2011
DOI: 10.1002/pmic.201100075
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of mouse sperm proteins correlated with epididymal maturation

Abstract: Sperm need to mature in the epididymis to become capable of fertilization. To understand the molecular mechanisms of mouse sperm maturation, we conducted a proteomic analysis using saturation dye labeling to identify proteins of caput and cauda epididymal sperm that exhibited differences in amounts or positions on two-dimensional gels. Of eight caput epididymal sperm-differential proteins, three were molecular chaperones and three were structural proteins. Of nine cauda epididymal sperm-differential proteins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 84 publications
1
50
1
2
Order By: Relevance
“…Thus, the energy pathway can affect sperm mobility in flagellum. Previous studies showed that spermatocytes and spermatids prefer oxidative phosphorylation for ATP production [22]. However, the oxygen partial pressure was found to be very low in this study.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Thus, the energy pathway can affect sperm mobility in flagellum. Previous studies showed that spermatocytes and spermatids prefer oxidative phosphorylation for ATP production [22]. However, the oxygen partial pressure was found to be very low in this study.…”
Section: Discussioncontrasting
confidence: 53%
“…Aldoa is a glycolysis enzyme that promotes reversible FBP cleavage to triose phosphate, G-3-P and DHAP. Aloda is in the mouse sperm flagellum accessory structures [22,23]. The flagellum is an important organ for sperm mobility.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been several attempts to conduct subcellular proteomic analyses of spermatozoa from the mouse (see [57][58][59][60][61]) and human sperm proteomes [9][10][11]15,26,27,[62][63][64][65][66][67][68] most of which reported less than 100 protein identifications. One of the more comprehensive lists published to date surveyed the entire sperm proteome and documented 1057 unique identifications [64].…”
Section: Discussionmentioning
confidence: 99%
“…Most of them have combined 2D gel electrophoresis and MS on the total extracts of immature and mature epididymal sperm from the mouse (Ijiri et al 2011), rat (Guo et al 2007), or hamster (Kameshwari et al 2010), or on subcellular compartments such as the head and flagella (Suryawanshi et al 2011), acrosomal and membranous proteins (Park et al 2012), and phosphopeptides (Baker et al 2012), or on purified sperm surface proteins (Belleannee et al 2011a). About 20 proteins involved in sperm maturation have been identified by these studies, of which only two or three have been found to be common between two studies or species.…”
Section: R31mentioning
confidence: 99%